CYA securing Exchange Server 2003 and Outlook Web Access : cover your a** by getting it right the first time - Walther, Henrik; Santry, Patrick (Rockland, MA : Syngress, 2004)
A highly portable, easily digestible road-map to configuring, maintaining and troubleshooting essential Exchange Server 2003 features. The book is organized around the 11 "MMCs" (Microsoft Management Consoles) that contain the configuration menus for the essential features. The options within each menu are explained clearly, potential problems are identified up-front, and configurations are subsequently presented in the aptly named "By the Book" section for that MMC. Readers will also appreciate the "Reality Check" sidebars throughout, which present valuable cost/benefit analyses of situations where there is no single "right" answer. * Walks the reader through step-by-step configurations to assure they have been thorough and responsible in their work * Clearly identifies those features of Exchange Server 2003 that represent the highest risk factors for attacks, performance degradation and service failures * CYA comes right out and says what most IT Professionals are already thinking.
Coverage includes: Exchange 2000 Administrative Rights, Mailbox Rights, Denial of Service and Exchange, Types of File Vulnerabilities, Vulnerability of Transmitted Data, Message Authenticity, Event Service and Event Sinks, Message Relay via SMTP, Preventing Exchange Security Problems, The W2K/IIS Platform Must Be Solid, Dedicate Servers to Specific Functions, Disable Unnecessary Services, Tightening Mailbox Security, Enabling SSL for Internet or Remote Clients, Locking Down an IIS/OWA Server, Imposing Limits, Protecting Critical Files, Network Analysis Risk Reduction, Denying Client Access, Stopping Viruses, Exchange 2000 and Firewalls, SMTP Security, Auditing for Possible Security Breaches, Windows 2000 Event Auditing, Exchange 2000 Event Auditing, Logging Internet Client Access, Securing MAPI Clients, Enabling Message Encryption (S/MIME).
Includes index.
Keywords: Microsoft Exchange server; Microsoft Outlook; Client/server computing; Computer networks -- Security measures; Electronic mail systems -- Security measures; Electronic books